(untitled) (Experimental biology, 2016)
Resistance of short stature sample line SIM79/279 and k-24/20989 inherited by the type of epistasis and complementary interaction of genes. Genes resistance to leaf rust SIM79/279 allelic to highly effective tester genes , Lr10, Lr26, Lr28, Lr29, Lr34, Lr39, Lr50 and line k-24/20989 - Lr1, Lr9, Lr10, Lr28, Lr29, Lr39, Lr50 of variety Thatcher. Main genes high resistance to leaf rust of lines SIM79/279 and k-24/20989 localized in chromosome 1B, 1A and 6B, 5D, respectively.